Mutu Pelayanan Pendidikan di Era Otonomi Daerah - Subiyakto, Rudi (Jurnal Ilmu Administrasi Negara (JUAN), 2014)
Education in Indonesia, since decentralization, has progressed seen from the role of local governmentand community autonomy. Efforts to improve the quality of education services by the centralgovernment issued a number of policies carried out by the application of Curriculum Education Unit,School-Based Management, standardize the quality of education through the National Agency forEducation Standards, and certification of teachers and lecturers. Implementation of these policiesdepends on how the local government's role in promoting education.